Simulation-Based Enhancement of Warehouse Layout and Inventory Control in An Indonesian Pharmaceutical Manufacturer - Indri Hapsari; Jerry Agus Arlianto; Peter Santoso (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: PT X, a pharmaceutical manufacturer in Indonesia, faces challenges in inventory management due to the lack of an optimal reorder system. This problem leads to overstock and high costs. Additionally, disorganized warehouse arrangements for packaging materials complicate retrieval and prolong order-picking times.Purpose: This study aims to optimize inventory management and improve warehouse layout to reduce costs and enhance operational efficiency.Design/methodology/approach: Inventory optimization was achieved using a two-pronged approach. The probabilistic Economic Order Quantity (EOQ) method was applied for items classified as Category A, while a periodic review method was used for items in Categories B and C. ABC analysis and demand forecasting informed the reorder quantities. A class-based storage system was implemented to improve warehouse layout, grouping packaging materials by type and organizing them sequentially according to ABC classification. Simulations in Promodel 6.0 compared warehouse conditions before and after improvements.Findings/Results: The optimized inventory system reduced total costs by 0.66%, from IDR26,809,071,104.17 to IDR26,630,856,055. The improved warehouse layout decreased order-picking time by 21.9%, from 19.14 minutes to 14.95 minutes, and reduced movement distances by 21.9%, from 1,469.97 meters to 1,148.03 meters.Conclusion: Integrating inventory optimization using a probabilistic EOQ and periodic review system with a class-based storage layout effectively reduces costs and enhances productivity in warehouse management. According to the ABC classification, the sequential arrangement significantly improves order-picking efficiency by reducing movement distances and time.Originality/Value (State of the Art): This study offers a novel combination of probabilistic EOQ, periodic review, and class-based storage, validated through simulation, to address inventory and warehouse management challenges in the pharmaceutical industry. The detailed quantitative analysis provides valuable insights into cost savings and operational improvements. Keywords: ABC analysis, class-based storage, inventory system, forecasting, warehouse simulation